Strategi dalam Konseling Pastoral di Era Digital: Studi Kasus Gereja-Gereja Kontemporer. - Aurelia Omersi; Erni Pamula Ranteallo; Rahel Lisa Sambara; Rosalinda Pamilangan; Patriani Lunga (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Counseling has experienced changes in its implementation process along with the progress and development of technology today. This research aims to explain strategies in Pastoral Counseling in the Digital Era: Case Studies of Contemporary Churches. This research uses a literature study with a case study approach. The results of this research show that there are 2 strategies in Pastoral Counseling in the Digital Era, namely strategies in the form of challenges, one of which is in the field of counseling. In this counseling, social media has become an important platform for communicating with the congregation.